Evaluation of total content phenolic, flavonoid and tannin of herbs used in treatment of ailments in Kisii and Nyamira Counties region, Kenya. - Moses A. Guto Maobe *; Leonard Gitu; Erastus Gatebe (Lorestan University of Medical Sciences, 2022)
Background and Aim: Herbs Carissa spinarum, Physalis minima and Toddalia asiati are used in the treatments of certain ailments in Kisii and Nyamira Counties region, Kenya but few studies have been conducted on the quality, efficacy and safety of using various parts of these herbs for these treatments. The principal aim of the present study was to standardize the three herbs of interest. This research was carried out to evaluate the total phenolic, flavonoid and tannin contents in the methanolic extract of whole plant Physalis minima, and leaves as wells roots of Carissa spinarum and Toddalia asiatica. Materials and Methods: Each part of the herb was extracted by soaking in methanol/dichloromethane in ratio 1:1 for seven days. Subsequently, it was filtered and concentrated by rotary vapor, and then the solvent allowed to escape and be solidified. The same process was repeated three times in all samples. Determination of the total phenolic content (mgGAE/g) was done by Folin-Ciocalteu on 765 nm using a spectrophotometer.The total flavonoid content (mgQE/g) was determined by aluminium chloride colorimetric assay on 415 nm. Total tannin content (mgCE/g) was analyzed by modified vanillin assay. Results: The highest and lowest levels of total phenolic content were observed in the roots of Toddalia asiatica and Carissa spinarum respectively. The highest and lowest levels of total flavonoid content were observed in Physalis minima and in the root of Carissa spinarum respectively. The highest and lowest levels of total tannin content were observed in the leaf extract of Toddalia asiatica and root extract of Carissa spinarum respectively. Conclusion: The highest total phenolic content was observed in the root extract of Toddalia asiatica.The highest total flavonoid content was observed in the extract of whole plant Physalis minima, while the highest total tannin content was observed in the leaf extract of Toddalia asiatica.